2010
DOI: 10.1007/s10775-010-9176-x
|View full text |Cite
|
Sign up to set email alerts
|

Vocational behavior and development in times of social change: new perspectives for theory and practice

Abstract: A review of new and emerging conceptions of work and career is complemented by a description of a comprehensive systems framework that avoids many of the dichotomies found in current accounts of career development and intervention. This is followed by a description of Ford and Smith's (Educational Psychologist 42(3):153-171, 2007) ''thriving with social purpose'' framework, which is offered as a potentially more inclusive approach to intervention than that based on the meta-theoretical framework of social cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…Consistent with the theory, we found that personal motivation varies on the basis of the changing contexts in the process of transition to full-time employment. This implies that young people actively adapt their career attitudes and such adaptive behavior supports the premise of MST that humans are selfconstructing, self-organizing, and self-regulating living systems (Ford & Smith, 2007;Vondracek et al, 2010). In addition, our findings also confirmed that emotions collaboratively act with negative perceptions toward the future, present, and past, coupled with a positive perception of future goal attainment (i.e., self-efficacy), can motivate job switching and job search.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Consistent with the theory, we found that personal motivation varies on the basis of the changing contexts in the process of transition to full-time employment. This implies that young people actively adapt their career attitudes and such adaptive behavior supports the premise of MST that humans are selfconstructing, self-organizing, and self-regulating living systems (Ford & Smith, 2007;Vondracek et al, 2010). In addition, our findings also confirmed that emotions collaboratively act with negative perceptions toward the future, present, and past, coupled with a positive perception of future goal attainment (i.e., self-efficacy), can motivate job switching and job search.…”
Section: Discussionsupporting
confidence: 83%
“…Although a career consciousness variable is not situated within the MST framework, the findings demonstrated the premise behind the theory that suggests the dynamic interactions between person and environment, proposing that individuals are both shaped by and shape their environment over a lifelong (Fouad & Kantamneni, 2008). As such, this study illustrated the core conception that mutually reinforcing patterns of goals, personal agency beliefs, and emotions can have powerful motivating effects leading individuals to engage in new challenges and opportunities (Ford & Smith, 2007;Vondracek et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…His work has demonstrated that a developmental-contextual perspective is necessary to understand why individuals choose certain jobs and careers and why some are more successful than others in a certain job and in the career as a whole. Fred, without a doubt, played a major role in championing the contextual view, which is also illustrated in his research on social change (Vondracek, Ferreira, & Santos, 2010) -the historical change in macro-context structure and how this macro-level change then affects vocational development at the individual level.…”
Section: We Observed Similar Trends When Comparing East and Westmentioning
confidence: 97%